2017
DOI: 10.4138/atlgeol.2016.013
|View full text |Cite
|
Sign up to set email alerts
|

<EM>Bifurculapes</EM> Hitchcock 1858: a revision of the ichnogenus

Abstract: Characters differentiating the arthropod trackway Bifurculapes from the similar ichnogenera Lithographus and Copeza include the position, arrangement and orientation of the tracks within the series. Of the five species of Bifurculapes originally described, only Bifurculapes laqueatus and Bifurculapes scolopendroideus are recognized herein; the other three ichnospecies are considered to be nomina dubia or junior subjective synonyms of Bifurculapes laqueatus. Two new specimens, recovered from the Early Jurassic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…(B) Asaphoidichnus trifidus (traced from Miller, 1880 ). (C) Bifurculapes laqueatus (traced from Getty, 2016 ). (D) Coenobichnus currani (traced from Walker, Holland & Gardiner, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) Asaphoidichnus trifidus (traced from Miller, 1880 ). (C) Bifurculapes laqueatus (traced from Getty, 2016 ). (D) Coenobichnus currani (traced from Walker, Holland & Gardiner, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
“…Kouphichnium , are also present. Ichnospecies of Bifurculapes have been variably attributed to insects, possibly beetles, and to crustaceans ( Getty, 2016 , 2018 ; Hitchcock, 1858 , 1865 ); ichnospecies of Diplichnites have been attributed to myriapods ( Briggs, Rolfe & Brannan, 1979 ; Davis, Minter & Braddy, 2007 ; Pollard, Selden & Watts, 2008 ; Shillito & Davies, 2018 ), notostracans ( Lucas et al, 2006a ; Minter et al, 2007 ), and other arthropods ( Melchor & Cardonatto, 2014 ; Minter et al, 2007 ); and ichnospecies of Kouphichnium have been attributed to limulids ( Caster, 1944 ; King, Stimson & Lucas, 2019 ; Lomax & Racay, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most subsequent workers (e.g., Hitchcock, 1889;Lull, 1915Lull, , 1953Mayoral, 2001) have also considered Bifurculapes to be an insect trackway. Getty (2016) suggested that the species B. laqueatus was likely the work of insects, and noted that the darkling beetle (Coleoptera: Tenebrionidae) trackways illustrated by Eiseman and Charney (2010) are similar to that ichnospecies. Demathieu et al (1992), however, argued that possible specimens from France were most likely made by a triopsid crustacean, and de Gibert et al (2000) proposed that their specimens were most likely made by astacid decapods.…”
Section: Trackmakersmentioning
confidence: 99%
“…C. H. Hitchcock (1889) reported Sagittarius, which is herein considered a junior subjective synonym of Bifurculapes, from Connecticut and New Jersey. Getty (2016) also reviewed the tentative occurrences of Bifurculapes from the Permian of France and Italy (Demathieu et al, 1992;Durand, 2001;Santi, 2006), the Triassic of Argentina (Melchor 2004), the Jurassic of Utah (Lucas et al, 2006;Milner et al, 2009), and the Cretaceous of Alaska (Fiorillo et al, 2009). He concluded that of these, the only specimen that should be included within Bifurculapes based on the information provided in the papers describing them was the one from Utah.…”
Section: Geographic and Stratigraphic Distributionmentioning
confidence: 99%
See 1 more Smart Citation